PENDAMPINGAN LEGALITAS USAHA, SPP-IRT, DAN SERTIFIKASI HALAL PRODUK UMKM DESA PAGELARAN, KECAMATAN MALINGPING, LEBAK, BANTEN - Maryam Jameelah; Ema Komalasari; Azzahra Putri Diandra; Sarah Giovanni; Yunus Efendi (UIN Sunan Kalijaga, 2022)
Business legality is one of the important things that becomes one of the foundations of legal certainty for Small and micro-scale enterprises. Many businesses are reluctant to register their business due to the complexity of the process. This phenomenon is the main problem in areas far away from the city. Pagelaran Village has various kinds of dry and wet-based food products that are widely traded and become local specialties, unfortunately, most of them are traded without a clear food label, and do not yet have business legality, SPP-IRT, and halal certificates. Mentoring activity is carried out using the interview method, filling the documents, and socializing various important matters related to business legal aspects. Based on the results of the mentoring activity, it can be seen that the mentoring process succeeded in achieving a 100% success rate for managing business legality, having food labels, and having SPP-IRT numbers. In addition, 50% of business actors are known to have obtained halal certificates for their products. This mentoring activity is expected to contribute to increasing the competitiveness of MSMEs in Indonesia.